The Influence of Family Characteristics, Family Financial Management, and Saving Intensity on The Size of Farmer Families’ Saving at Ciaruteun Ilir Villages - Kartikasari, Susanti; Muflikhati, Istiqlaliyah (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2016)
The aim of this study was to analyze the influence of financial management on saving behavior in farmer families. This research uses cross-sectional design conducted in Ciaruteun Ilir Village with purposive selection location. The study was performed in 70 randomly selected families with working wife. The results showed that financial management of farmer family is poor. A total of 71.4 percent of farmer families has saving. The results of multiple linear regression showed that the bigger the family size, the weaker the financial management. Nonetheless, the number of assets and higher family income would increase financial management. Logistic regression showed that family with better financial management is more likely to have better saving. Family size would reduce saving, while family income would increase saving.